2014
DOI: 10.1371/journal.pone.0088145
|View full text |Cite|
|
Sign up to set email alerts
|

The Sulfated Laminarin Triggers a Stress Transcriptome before Priming the SA- and ROS-Dependent Defenses during Grapevine's Induced Resistance against Plasmopara viticola

Abstract: Grapevine (Vitis vinifera) is susceptible to many pathogens which cause significant losses to viticulture worldwide. Chemical control is available, but agro-ecological concerns have raised interest in alternative methods, especially in triggering plant immunity by elicitor treatments. The β-glucan laminarin (Lam) and its sulfated derivative (PS3) have been previously demonstrated to induce resistance in grapevine against downy mildew (Plasmopara viticola). However, if Lam elicits classical grapevine defenses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 71 publications
7
83
0
1
Order By: Relevance
“…Fucans enhanced ROS production as well as the accumulation of salicylic acid and antimicrobial compounds in tobacco (Klarzynski et al, 2003). Recently, Gauthier et al (2014) showed that upon inoculation of grapevine with Plasmopara viticola, sulphated laminarins were able to prime ROS-dependent defence pathways leading to enhanced resistance against downy mildew. Thus, we can speculate that the ability of the SE used here to prime for ROS and antioxidant defences is may be due, at least, to their higher content of polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Fucans enhanced ROS production as well as the accumulation of salicylic acid and antimicrobial compounds in tobacco (Klarzynski et al, 2003). Recently, Gauthier et al (2014) showed that upon inoculation of grapevine with Plasmopara viticola, sulphated laminarins were able to prime ROS-dependent defence pathways leading to enhanced resistance against downy mildew. Thus, we can speculate that the ability of the SE used here to prime for ROS and antioxidant defences is may be due, at least, to their higher content of polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ulvan could induce resistance in several plants such as apple against blue mold by Penicillium expansum Link (blue mold) and Botrytis cinerea inducing the activation of CAT and SOD, PAL, POX and polyphenoloxydase (PPO) as well as the levels of lignin and phenolic compounds (Abouraïcha et al, 2015). These studies and others with chemical sulfation of laminarin, suggested that the enhancement of defense responses by algae extracts can be related to its sulfate residue (El Modafar et al, 2012;Gauthier et al, 2014).…”
Section: Algi Extracts: Ulvan and Laminarinmentioning
confidence: 94%
“…They were subsequently bleached first with pure methanol at least 2 days and then chloral hydrate solution (1.0 g/L) for 12–24 h until they become completely transparent. Infection sites (corresponding to encysted zoospores) were detected after aniline blue staining (Gauthier et al , ). Four representative fields of each disc and ten discs per condition were observed by epifluorescence microscopy [magnification ×200, λexc = 340–380 nm, λem = 425 nm (long pass filter)].…”
Section: Methodsmentioning
confidence: 99%